The Influence of Using Medication Calendar on Driving Compliance In Patients with Diabetes Mellitus in Meninting Village - Rusmini Rusmini; Moh Arip; Desty Emilyani; Linda Amelia Sari (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2023)
Medication calendar or commonly known as functional calendar is a media that specifically designed to improve adherence to taking medication by adding several special features such as patient names, drug names, and hours of taking medication. The purpose of this study was to determine the effect of using the medication calendar in increasing medication adherence in diabetes mellitus patients. This research used a pre-experimental research design with one group pretest and posttest design approach. The sampling technique used was simple random sampling. The sample was 30 respondents. Compliance in taking medication was obtained using the MMAS-8 questionnaire. The data of patients’ medication adherence before and after using medication calendar, was analyzed using the Wilcoxon Signed Rank Test. The results showed that there was a difference in the medication adherence level before and after the medication calendar intervention with a value of p = 0.000 < α = 0.05. The use of medication calendar is proven to be able to influence the medication adherence in diabetes mellitus patients. This tool can be an alternative way to increase medication adherence, as part of an important pillar in the management of Diabetes Mellitus.